Methods for making induced pluripotent stem cells: reprogramming à la carte - González, Federico; Boué, Stéphanie; Belmonte, Juan Carlos Izpisúa (Nature reviews. Genetics, 2011)
Key Points Direct reprogramming enables the generation of pluripotent stem-cell lines from almost any somatic tissue and mammalian species, thereby avoiding the ethical issues associated with human embryonic stem cells. Although direct reprogramming is conceptually and technically simple, it is an extremely slow and inefficient process. It is influenced by several variables that affect its efficiency and reproducibility, and the quality of the resulting induced pluripotent stem cells (iPSCs). Depending on the donor cell type, reprogramming is achieved with different efficiencies and kinetics. These differences are attributed to variations in the endogenous levels of certain reprogramming factors, differentiation status and/or intrinsic epigenetic states that are more amenable to reprogramming. Different factors are able to promote reprogramming, including genes that are normally expressed in early development, factors that directly or indirectly affect cell proliferation, chromatin remodellers or microRNAs. At present in the iPSC field, it is still difficult to unambiguously designate a reprogramming strategy that is fitting for all purposes. In each case, one will have to evaluate the most appropriate starting cell types, factors, culture conditions and delivery method. Reprogramming methods can be divided into two classes, those involving the integration of exogenous genetic material and those involving no genetic modification of the donor cells. Among these methodologies, retroviral delivery of OCT4 , SOX2 , KLF4 and MYC (the OSKM set) into fibroblasts is still the most widely used. Integrative reprogramming approaches generate heterogeneous iPSC lines, which could obscure comparative analysis between lines. The use of Cre-deletable vectors has partially solved this problem. Among non-integrative reprogramming systems, the recently published RNA-based approach seems promising on the basis of the high efficiency it achieves. Although appealing, the high gene dosages of the reprogramming factors resulting from direct messenger RNA delivery may represent an oncogeneic risk owing to higher expression levels of MYC . A crucial challenge in the iPSC field is to evaluate how these various methodologies affect the quality of iPSCs in terms of transcriptional signatures, epigenetic status, genomic integrity, stability, differentiation and tumorigenic potential. Whole-genome sequencing platforms will probably have an important role in the future in assessing the integrity of the genome of iPSCs and will certainly improve our understanding of the mechanism by which reprogramming occurs in a specific cell type. There are now myriad variations on techniques to reprogramme somatic cells into pluripotent stem cells, but which options should researchers choose? This Review sets out the choices, focusing on how the desired downstream application should guide the reprogramming strategy. Pluripotent stem-cell lines can be obtained through the reprogramming of somatic cells from different tissues and species by ectopic expression of defined factors. In theory, these cells — known as induced pluripotent stem cells (iPSCs) — are suitable for various purposes, including disease modelling, autologous cell therapy, drug or toxicity screening and basic research. Recent methodological improvements are increasing the ease and efficiency of reprogramming, and reducing the genomic modifications required to complete the process. However, depending on the downstream applications, certain technologies have advantages over others. Here, we provide a comprehensive overview of the existing reprogramming approaches with the aim of providing readers with a better understanding of the reprogramming process and a basis for selecting the most suitable method for basic or clinical applications.